Wood-collagen-hydroxyapatite scaffold as well as preparation method and application thereof

By using the method of using wood and vacuum-impregnated collagen to prepare a wooden-collagen-hydroxylhstone bench with a height of the height of the opposite sex and super mechanical strength, the existing materials cannot effectively effectively bionic bone tissue complicated structure The problem achieves significant cells into osteoma and bone regeneration effects.

CN119367600APending Publication Date: 2025-01-28JIANGSU LANJI LIFE TECHNOLOGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311656563.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-05
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing collagen-hydroxyapatite scaffolding materials cannot effectively biomimetic the complex nanostructure of bone tissue, and nano-hydroxyapatite is prone to aggregation, affecting its biocompatibility and osteogenetic differentiation effect.

Method used

The use of wood quality as the substrate is used as a substrate, and collagen and mineralized hydroxylhhexylite are prepared through vacuum-soaked collagen and in-situ.

Benefits of technology

This bracket material significantly promotes the adhesion, proliferation and osteomaization of cells, can effectively promote the treatment of bone regeneration, bone growth, and bone maturity, and it is suitable for the treatment of clinical bone defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119367600A_ABST
    Figure CN119367600A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of biomedical materials, and particularly relates to a wood-collagen-hydroxyapatite scaffold, a preparation method and application, and the wood-collagen-hydroxyapatite scaffold has high anisotropy and excellent mechanical strength; the hydrogel has remarkable biocompatibility and biological activity, and can promote adhesion, proliferation and osteogenic differentiation of cells; bone regeneration, bone ingrowth and bone maturation can be promoted; the medicine can be applied to clinical treatment of bone defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to a wood-collagen-hydroxyapatite scaffold, a preparation method and an application thereof. Background Art

[0002] Bone defects are usually a serious pathological condition caused by trauma, infection or tumor resection. Due to the limited self-regeneration ability of bone tissue, timely and effective surgical intervention is required for large or critical-sized bone defects. Traditional autologous bone transplantation and allogeneic bone transplantation are widely used in the clinical treatment of bone defects, but they have significant defects, such as limited tissue sources, donor site complications and immune rejection reactions.

[0003] Biomimetic materials based on tissue engineering, especially collagen-hydroxyapatite scaffolds, have attracted widespread attention in bone tissue engineering due to their good biocompatibility and bioactivity. Composite scaffolds of collagen and nano-hydroxyapatite have been developed and applied to the treatment of bone defects. For example, invention patent CN201910177807.5 discloses a porous bone repair scaffold material, but its nano-hydroxyapatite is prone to aggregation. Although in situ mineralization technology can prepare collagen scaffold materials with uniformly distributed hydroxyapatite, these collagen-hydroxyapatite scaffold materials can only biomimetic the basic composition of natural bones, but cannot biomimetic the complex nanostructure of bone tissue.

[0004] Natural bone has a multi-scale hierarchical structure and an inherent anisotropic structure, which play an important role in promoting cell adhesion, migration and osteogenic differentiation. Anisotropic scaffold materials such as chitosan-graphene oxide, orthophosphosilicate glass-polylactic acid and hydroxyapatite-polyamide 66 have been developed for bone tissue regeneration. However, anisotropic scaffolds based on collagen-hydroxyapatite are rarely reported.

[0005] The inventor unexpectedly discovered that by using delignified wood as a matrix, vacuum impregnation of collagen and in-situ mineralized hydroxyapatite, a wood-collagen-hydroxyapatite scaffold with high anisotropy and super mechanical strength can be prepared. The scaffold material has excellent biocompatibility and bioactivity, and can significantly promote cell adhesion, proliferation and osteogenic differentiation. In a rabbit femoral defect model, the scaffold material can promote bone tissue regeneration, bone ingrowth into the scaffold, and bone tissue maturation. Summary of the invention

[0006] In view of the above technical problems, the object of the present invention is to provide a method for preparing a wood-collagen-hydroxyapatite scaffold, the preparation method comprising the following steps: (1) soaking the wood in a 2-8wt% NaClO2 solution, reacting at 60°C for 24-72 hours to delignify, washing with ethanol, and freeze-drying;

[0007] (2) immersing the wood obtained in step (1) in a 0.5-5 mg / mL collagen solution, evacuating the solution, and freeze-drying the solution to obtain wood coated with collagen;

[0008] (3) The collagen-coated wood obtained in step (2) is mineralized alternately in 500-1000 mM CaCl2 solution and 300-600 mM Na2HPO4 / NaH2PO4 solution at 37°C for 3-8 days, washed thoroughly, and freeze-dried to obtain a wood-collagen-hydroxyapatite scaffold.

[0009] Preferably, the collagen is animal collagen or recombinant collagen.

[0010] Preferably, the animal collagen includes one or more of type I, type II, and type III.

[0011] Preferably, the animal collagen is yak type I collagen.

[0012] Preferably, the concentration of the NaClO2 solution in step (1) is 3%-5%.

[0013] The second object of the present invention is to provide a wood-collagen-hydroxyapatite scaffold prepared by the preparation method of the wood-collagen-hydroxyapatite scaffold.

[0014] The third object of the present invention is to provide the use of the wood-collagen-hydroxyapatite scaffold in bone tissue regeneration.

[0015] The fourth object of the present invention is to provide the use of the wood-collagen-hydroxyapatite scaffold in preparing artificial bone repair materials.

[0016] The fifth object of the present invention is to provide the use of the wood-collagen-hydroxyapatite scaffold as or in the preparation of one or more of the following bone defect filling materials: bone defects in maxillofacial surgery, bone defects in dental surgery, skull defects, various closed fracture bone defects in the limbs, and spinal defects.

[0017] The beneficial effects of the present invention are as follows: the present invention provides a method for preparing a wood-collagen-hydroxyapatite scaffold, and the prepared wood-collagen-hydroxyapatite scaffold has high anisotropy and excellent mechanical strength; has significant biocompatibility and bioactivity, can promote cell adhesion, proliferation and osteogenic differentiation; can promote bone regeneration, bone ingrowth and bone maturation; and can be applied to the treatment of bone defects in clinical practice. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Morphological characterization of scaffold materials Note: WW: white wood; WC: wood-collagen; WCH: wood-collagen-hydroxyapatite; A is the surface photo of the scaffold material; B is the SEM image of the scaffold material in the L and R directions

[0019] Figure 2 Compositional characterization of scaffold materials

[0020] Note: A is the FT-IR image of the scaffold material; B is the XRD image of the scaffold material

[0021] Figure 3 Mechanical properties of stent materials Note: A is the compressive strength of the stent in the L and R directions; B is the tensile strength of the stent in the L and R directions; Figure 4 Live / dead cell staining of bone marrow mesenchymal stem cells cultured on scaffold materials

[0022] Figure 5 Immunofluorescence staining of bone marrow mesenchymal stem cells cultured on scaffold materials

[0023] Figure 6 Expression of osteogenic genes in bone marrow mesenchymal stem cells cultured on scaffold materials Note: A: Relative expression of ALP gene in the L and R directions of the scaffold; B: Relative expression of Col1a1 gene in the L and R directions of the scaffold; C: Relative expression of Runx 2 gene in the L and R directions of the scaffold

[0024] Figure 7 Micro-CT images of scaffold material implanted into rabbit femoral defect

[0025] Note: A is a 3D Micro-CT image; B is a 2D Micro-CT image

[0026] Figure 8 Histological staining of rabbit femoral defect repaired with scaffold material

[0027] Note: A is H&E tissue staining; B is Masson tissue staining DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] It should be noted that the reagents used in the following examples, unless otherwise specified, can be purchased from the market.

[0030] In the following embodiments, it should be noted that WW is the abbreviation for white wood; WC is the abbreviation for wood-collagen; and WCH is the abbreviation for wood-collagen-hydroxyapatite. In some embodiments and drawings of the specification, the abbreviations are directly used instead of the full names, which have the same meaning.

[0031] The wood described in the present invention is a general term for wood and timber, and is not limited to a certain type of wood. Common wood can be used, such as balsa wood, basswood, and arbor.

[0032] Example 1 Preparation of wood-collagen-hydroxyapatite (WCH) scaffold

[0033] (1) Natural wood was immersed in a 2 wt% NaClO2 solution and reacted at 60°C for 72 hours for delignification. Then, the wood was washed with ethanol and freeze-dried to obtain white wood (WW).

[0034] (2) The white wood (WW) was immersed in a 0.5 mg / mL yak type I collagen solution, and vacuum was applied to allow the yak type I collagen solution to penetrate into the WW, and then freeze-dried to form collagen-coated white wood (WC).

[0035] (3) The WC scaffolds were alternately mineralized in 500 mM CaCl2 solution and 300 mM Na2HPO4 / NaH2PO4 solution at 37°C for 8 days. After being fully washed, they were freeze-dried to obtain wood-collagen-hydroxyapatite (WCH) scaffolds.

[0036] The morphologies of the prepared WW, WC and WCH scaffolds are shown in Figure 2. Figure 1 As shown in A. The delignified WW is a white scaffold material, the surface of the WC scaffold coated with collagen is smoother, and the surface of the WCH scaffold with in situ mineralized hydroxyapatite forms a white precipitate.

[0037] Example 2 Preparation of wood-collagen-hydroxyapatite (WCH) scaffold

[0038] (4) The natural wood was immersed in 8 wt% NaClO2 solution and reacted at 60°C for 24 hours to perform delignification, and then washed with ethanol and freeze-dried to obtain white wood (WW).

[0039] (5) The white wood (WW) was immersed in a 5 mg / mL yak type I collagen solution, and vacuum was applied to allow the yak type I collagen solution to penetrate into the WW, which was then freeze-dried to form collagen-coated white wood (WC).

[0040] (6) The WC scaffolds were alternately mineralized in 1000 mM CaCl2 solution and 600 mM Na2HPO4 / NaH2PO4 solution at 37°C for 3 days. After being fully washed, they were freeze-dried to obtain wood-collagen-hydroxyapatite (WCH) scaffolds.

[0041] Example 3 Morphological Characterization of Wood-Collagen-Hydroxyapatite (WCH) Scaffolds

[0042] The WW, WC and WCH brackets prepared in Example 1 were fixed on the sample stage, and after gold spraying for 25 seconds, the sample morphology was detected using a scanning electron microscope (SEM) at a voltage of 5.0 kV.

[0043] The results of scanning electron microscopy are as follows Figure 1 As shown in B, the WW, WC and WCH scaffolds have parallel pore structures in the L direction and interconnected porous structures in the R direction; the WC scaffold presents a white collagen coating in the L and R directions; the WCH scaffold has hydroxyapatite nanoparticles uniformly deposited in the L and R directions.

[0044] Example 4 Composition Characterization of Wood-Collagen-Hydroxyapatite (WCH) Scaffold

[0045] (1) The WW, WC and WCH scaffolds prepared in Example 1 were mixed and ground with potassium bromide particles at a mass ratio of 1:100, and then the powders were pressed into transparent sheets for Fourier transform infrared (FT-IR) measurement.

[0046] The results are as follows Figure 2 As shown in A, the WW bracket is at 3408cm -1 Characteristic hydroxyl peak; the hydroxyl peak in the WC scaffold is red-shifted to 3438cm -1 ;WCH bracket at 1024cm -1 、602cm -1 and 563cm -1 The characteristic peaks that appeared were attributed to the phosphate groups. These results indicate that the formation of WCH scaffolds involves the successful coating of collagen and the in situ mineralization of hydroxyapatite.

[0047] (2) The WCH scaffold prepared in Example 1 was placed on a powder X-ray diffractometer (XRD) and its crystal structure type was determined at a scanning rate of 0.02° / s.

[0048] The results are as follows Figure 2 As shown in Figure B, the WW and WC scaffolds only have characteristic peaks at 16.5° and 22.5°, which correspond to the diffraction planes (101) and (002) of cellulose crystals; the WCH scaffold has characteristic peaks different from those of WW and WC at 26.4°, 32.3°, 39.8°, 46.9° and 49.8°, which correspond to the diffraction planes (002), (211), (310), (222) and (213) of hydroxyapatite, respectively. These results indicate that hydroxyapatite is mineralized in situ in the WCH scaffold.

[0049] Example 5 Mechanical properties of wood-collagen-hydroxyapatite (WCH) scaffolds

[0050] (1) Balsa wood was cut along the L direction and the R direction to form samples with a size of 8 mm×8 mm×4 mm, and then WW, WC and WCH brackets were prepared according to the steps of Example 1. Finally, a compression test was carried out at a speed of 1 mm / min.

[0051] The results are as follows Figure 3 As shown in A, the compressive strengths of WW, WC and WCH brackets in the L direction are 0.9 MPa, 1.6 MPa and 5.5 MPa, respectively, and the compressive strengths in the R direction are 0.3 MPa, 0.8 MPa and 2.9 MPa, respectively.

[0052] (2) The balsa wood was cut along the L direction and the R direction to form samples with a size of 50 mm×6 mm×2 mm, and then WW, WC and WCH brackets were prepared according to the steps of Example 1. Finally, a tensile test was carried out at a speed of 1 mm / min.

[0053] The results are as follows Figure 3 As shown in B, the tensile strengths of WW, WC, and WCH scaffolds in the L direction are 7.4 MPa, 9.0 MPa, and 23.3 MPa, respectively, and the tensile strengths in the R direction are 0.5 MPa, 0.6 MPa, and 2.1 MPa, respectively. These results indicate that the WCH scaffold has excellent mechanical strength and high anisotropy.

[0054] Example 6 Cell proliferation of wood-collagen-hydroxyapatite (WCH) scaffolds

[0055] The rat bone marrow mesenchymal stem cells (BMSCs) attached to the wall were digested with trypsin to form a density of 1×10 6cells / mL suspension. They were then planted on the surface of WW, WC and WCH scaffold materials and cultured in α-MEM complete medium. After 7 days, live cells and dead cells were stained with Calcein-AM and Propidium Iodide (PI) at 37°C for 1 hour. Finally, cell fluorescence images were obtained by laser confocal microscopy.

[0056] The results are as follows Figure 4 As shown, the live / dead cell staining images of BMSCs cultured in the L direction of WW, WC and WCH scaffold materials for 1 day, 4 days and 7 days, and in the R direction for 7 days, respectively. The results showed that with the increase of culture time, the number of live cells in the L direction of WW, WC and WCH scaffold materials showed an increasing trend; compared with WW and WC scaffolds, WCH scaffolds had significantly higher numbers of live cells; compared with WCH scaffolds in the R direction, cells in WCH scaffolds in the L direction grew along parallel channels and had more live cells. The results showed that the WCH scaffold in the L direction had excellent biocompatibility and could significantly promote cell proliferation.

[0057] Example 7 Cell Adhesion to Wood-Collagen-Hydroxyapatite (WCH) Scaffolds

[0058] The density is 1×10 6 BMSCs suspensions of 10 cells / mL were seeded onto the surface of WW, WC and WCH scaffold materials in the L and R directions, respectively, and cultured in α-MEM complete medium for 7 days. They were fixed with 4% formaldehyde for 15 minutes and permeabilized with 0.1% Triton X-100 for 5 minutes; they were blocked with 1% BSA in PBS buffer (10mM, pH 7.2-7.4) at room temperature for 30 minutes; the cell actin skeleton was stained with 100nM rhodamine-labeled phalloidin for 1 hour, and then 5μg / mL Hoechst33258 was added to stain the cell nucleus for 5 minutes. After staining, fluorescence images were captured using a laser confocal microscope.

[0059] The results are as follows Figure 5As shown, the immunofluorescence staining images of BMSCs cultured in the L and R directions of WW, WC and WCH scaffolds for 7 days are shown. The results show that BMSCs adhered to the L direction of the WCH scaffold have a delicate actin cytoskeleton structure and the number of adhered cells is the largest; BMSCs adhered to the L direction of the WC scaffold have a good actin cytoskeleton structure, but the number of adhered cells is reduced; while the cytoskeleton structure of the WW group is not well developed and the number of cells is the least. Compared with the scaffold material in the L direction, the cell diffusion area of ​​the scaffold material in the R direction is small and the number of cells is small. The results show that the WCH scaffold provides cells with a bioactive scaffold that can effectively promote the adhesion and diffusion of BMSCs.

[0060] Example 8 Cell differentiation of wood-collagen-hydroxyapatite (WCH) scaffolds

[0061] The density is 1×10 6 The suspension of cells / mL was implanted into the WW, WC and WCH scaffold materials in the L and R directions respectively, and cultured in α-MEM complete medium for 14 days. Total RNA was extracted using RNA isolation kit, cDNA was synthesized using PrimeScript RT reagent Kit and gDNA Eraser, gene expression levels were analyzed using TB Green Premix Ex Taq II, and the expression of cartilage-specific genes was detected using Real-Time PCR System. -ΔΔCT The relative expression of the target gene was calculated by the method, with β-actin as the internal reference gene, and normalized according to the gene expression of the WW scaffold in the R direction on the 14th day.

[0062] The results are as follows Figure 6 As shown, AC is the relative expression of ALP, Col1a1 and Runx 2 genes in the L and R directions of the scaffolds, respectively. The results showed that after 14 days of cell culture, the relative expression of ALP gene increased by 1.7 times in the R direction of the WCH scaffold and 2.5 times in the L direction; the relative expression of Col1a1 gene increased by 2.0 times in the R direction of the WCH scaffold and 3.0 times in the L direction; the relative expression of Runx 2 gene increased by 1.5 times in the R direction of the WCH scaffold and 2.8 times in the L direction. The results showed that the WCH scaffold had excellent biological activity and significantly promoted the osteogenic differentiation of BMSCs; compared with the R direction of the WCH scaffold, the L direction of the WCH scaffold had a better osteogenic differentiation ability.

[0063] Example 9 Tissue regeneration of wood-collagen-hydroxyapatite (WCH) scaffolds

[0064] Male New Zealand white rabbits (2.5-3 kg) were housed in a standard laboratory. Anesthesia was performed by intravenous injection of 2% (w / v) sodium pentobarbital (30 mg / kg) into the ear vein. After shaving and disinfection of the surgical site, a 3 cm skin incision was made, and the femur was exposed by separating the muscle and fascia. A cylindrical bone defect (3 mm in diameter × 2 mm in height) was created in the cortical bone of the femur surface using a skull drill and continuously flushed with saline. The L direction of the WW, WC, and WCH scaffolds and the R direction of the WCH scaffold were implanted into the defect site along the longitudinal direction of the femur, and then the synovial bursa and skin were sutured. After 12 weeks of implantation, the rabbits were euthanized by an overdose of sodium pentobarbital. After the collected specimens were fixed in 4% formaldehyde for 48 hours, the femoral structure was scanned using a Micro-CT imaging device. The scanning voltage was 40 kV, the current was 250 μA, the exposure time was 240 ms, and the slice thickness was 0.1 mm.

[0065] The results are as follows Figure 7 As shown, A and B are the 3D and 2D images of Micro-CT, respectively. The results show that there is only a small amount of new bone tissue around the WW scaffold in the L direction; the regenerated bone tissue of the WC scaffold in the L direction is relatively increased; the WCH scaffold in the L direction has significant bone tissue regeneration around it; and the WCH scaffold in the R direction has relatively less regenerated new bone tissue compared with the WCH scaffold in the L direction. These results show that the WCH scaffold has excellent osteoinductive activity and can accelerate tissue regeneration around bone defects.

[0066] Example 10 Histological staining of wood-collagen-hydroxyapatite (WCH) scaffold-induced bone regeneration

[0067] (1) The fixed samples were treated in 10% EDTA solution for 14 days for complete decalcification. The samples were then dehydrated in alcohol gradients, embedded in paraffin and sliced ​​into 5 μm thin slices, and the tissue sections were stained with hematoxylin & eosin (H&E).

[0068] The results are as follows Figure 8 As shown in A, the WW scaffold group in the L direction had basically no obvious bone tissue growth into the scaffold; the WC scaffold in the L direction had less bone growth; the WCH scaffold in the L direction had obvious bone tissue growth; and the WCH scaffold in the R direction had significantly less bone growth into the scaffold compared with the WCH scaffold in the L direction. The results show that the WCH scaffold in the L direction can significantly promote the growth of bone tissue into the scaffold.

[0069] (2) The fixed samples were treated in 10% EDTA solution for 14 days for complete decalcification. The samples were then dehydrated in alcohol gradients, embedded in paraffin and sliced ​​into 5 μm slices, and the tissue sections were subjected to Masson staining.

[0070] The results are as follows Figure 8 As shown in B. The WW scaffold group in the L direction had almost no mature bone tissue; the WC scaffold group in the L direction had a small amount of mature bone tissue; the WCH scaffold group in the L direction had a large amount of mature bone tissue; and the WCH scaffold group in the R direction had relatively little mature bone tissue. The results showed that the WCH scaffold in the L direction could significantly promote the maturation of bone tissue.

[0071] In summary, the present invention provides a method for preparing a wood-collagen-hydroxyapatite scaffold. The wood-collagen-hydroxyapatite scaffold prepared by the method has high anisotropy and excellent mechanical strength. The scaffold material has significant biocompatibility and bioactivity, and can promote cell adhesion, proliferation and osteogenic differentiation. In addition, the scaffold can promote bone regeneration, bone ingrowth and bone maturation, and has great potential in the treatment of bone defects in clinical practice.

Claims

1. A method for preparing a wood-collagen-hydroxyapatite scaffold, characterized in that: The preparation method comprises the following steps: (1) soaking wood in a 2-8wt% NaClO2 solution, reacting at 60°C for 24-72 hours to delignify, washing with ethanol, and freeze-drying; (2) immersing the wood obtained in step (1) in a 0.5-5 mg / mL collagen solution, evacuating the solution, and freeze-drying the solution to obtain wood coated with collagen; (3) The collagen-coated wood obtained in step (2) is mineralized alternately in 500-1000 mM CaCl2 solution and 300-600 mM Na2HPO4 / NaH2PO4 solution at 37°C for 3-8 days, washed thoroughly, and freeze-dried to obtain a wood-collagen-hydroxyapatite scaffold.

2. The method for preparing the wood-collagen-hydroxyapatite scaffold according to claim 1, characterized in that: The collagen is animal collagen or recombinant collagen.

3. The method for preparing the wood-collagen-hydroxyapatite scaffold according to claim 1, characterized in that: The animal collagen includes one or more of type I, type II and type III.

4. The method for preparing the wood-collagen-hydroxyapatite scaffold according to claim 1, characterized in that: The animal collagen is yak type I collagen.

5. The method for preparing the wood-collagen-hydroxyapatite scaffold according to claim 1, characterized in that: The concentration of the NaClO2 solution in step (1) is 3%-5%.

6. A wood-collagen-hydroxyapatite scaffold prepared by the method for preparing a wood-collagen-hydroxyapatite scaffold according to any one of claims 1 to 5.

7. Use of the wood-collagen-hydroxyapatite scaffold as claimed in claim 6 in bone tissue regeneration.

8. Use of the wood-collagen-hydroxyapatite scaffold as claimed in claim 6 in preparing artificial bone repair materials.

9. Use of the wood-collagen-hydroxyapatite scaffold as claimed in claim 6 as or in the preparation of one or more of the following bone defect filling materials: bone defects in maxillofacial surgery, bone defects in dental surgery, skull defects, various closed fracture bone defects in limbs, and spinal defects.

Citation Information

Patent Citations

  • Porous bone repair stent material and preparation method thereof

    CN109908405A